Faktor-Faktor Yang Berhubungan Dengan Kecemasan Keluarga Pasien Di Ruang Intensive Care Unit RSUD Banyumas - Setyaningsih, Sa'diyah; Fatwati Fitriana, Nurul (Universitas Kadiri, 2024)
Background: ICU care can lead to anxiety for patients' families. Anxiety is influenced by factors such as age, gender, experience of accompanying patients in the ICU, education level, family relationships, medical diagnosis, and health insurance coverage. Objective: To determine factors associated with family anxiety in the Intensive Care Unit (ICU) of RSUD Banyumas (Banyumas Regional Public Hospital). Method: This study is descriptive correlational research using a cross-sectional approach. The study sample consisted of 38 family members of patients treated in the ICU, selected using the Consecutive Sampling technique. The research analysis used the Mann-Whitney U test. Results: The correlation between age and anxiety had a p-value of 0.66, the relationship between gender and anxiety had a p-value of 0.635, the relationship between experience of accompanying patients and anxiety had a p-value of 0.002, the relationship between education level and anxiety had a p-value of 0.409, the relationship between family relationship with the patient and anxiety had a p-value of 0.270, the relationship between patient's medical diagnosis and anxiety had a p-value of 0.464, and the correlation between health insurance coverage status and anxiety had a p-value of 0.765. Conclusion: The factor associated with family anxiety in the ICU of Banyumas Regional General Hospital is the experience of accompanying patients in the ICU. Keywords: Anxiety, ICU, age, gender, experience in accompanying patients in ICU, education level, family relationships, medical diagnosis, health insurance coverage status